Cancer incidence and mortality among patients with new-onset atrial fibrillation: A population-based matched cohort study - Nadine Zakkak; Matthew Barclay; Arturo Gonzalez-Izquierdo; Amand Floriaan Schmidt; Gregory Y.H. Lip; Georgios Lyratzopoulos; Rui Providencia (Neoplasia: An International Journal for Oncology Research)
Background: Understanding the risk of cancer after the diagnosis of another condition can present opportunities for earlier diagnosis. We examined the risk of cancer diagnosis conditional on prior diagnosis of atrial fibrillation (AF). Methods: Linked electronic health records were used to identify patients aged ≥18 with new-onset AF and age-sex-matched controls. Cumulative incidence of and mortality from cancer (overall and cancer-site specific) within three months, three months to five years and beyond five years from diagnosis of AF were examined. Findings were further validated using Mendelian randomisation (MR). Results: The cohort included 117,173 patients with new-onset AF and 117,173 matched controls (median age 78). In the first three months, 2.2% of AF patients were diagnosed with cancer vs. 0.47% in controls (relative risk: 4.7 [95%CI 4.2-5.4] in men and 4.4 [95%CI 3.8-5.0] in women). Nearly 80% of cancers related to thoracic or abdominal organs. Differences in cumulative incidence were only evident in women between three months and five years (subdistribution hazard ratio=1.1 [95%CI 1.01-1.12]) and absent in all patients beyond five years. MR analysis did not support the presence of a causal association between AF and major cancer subtypes. Conclusion: There is a large short-term increase in cancer incidence and mortality following new-onset AF. The findings may reflect incidental identification of AF or paraneoplastic manifestation. New-onset AF confers high short-term risk of cancer diagnosis, at levels comparable with symptomatic risk threshold mandating urgent assessment for suspected cancer.